2022
DOI: 10.3390/membranes12020113
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Sensing Ion Channel 2: Function and Modulation

Abstract: Acid-sensing ion channels (ASICs) have an important influence on human physiology and pathology. They are members of the degenerin/epithelial sodium channel family. Four genes encode at least six subunits, which combine to form a variety of homotrimers and heterotrimers. Of these, ASIC1a homotrimers and ASIC1a/2 heterotrimers are most widely expressed in the central nervous system (CNS). Investigations into the function of ASIC1a in the CNS have revealed a wealth of information, culminating in multiple contemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 144 publications
(345 reference statements)
0
10
0
1
Order By: Relevance
“…Furthermore, genetic studies in humans of a closely related gene ASIC1a have previously demonstrated a link between variants, panic disorder (68), and amygdala volume (69). Although ASIC2 is less well studied or lacked adequate power (70) compared to ASIC1a, there is evidence suggesting that ASIC2 works in concert and regulates neuroplasticity in the brain (71, 72). ASICs are considered potential drug targets in various somatic and psychiatric conditions (64, 72, 73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, genetic studies in humans of a closely related gene ASIC1a have previously demonstrated a link between variants, panic disorder (68), and amygdala volume (69). Although ASIC2 is less well studied or lacked adequate power (70) compared to ASIC1a, there is evidence suggesting that ASIC2 works in concert and regulates neuroplasticity in the brain (71, 72). ASICs are considered potential drug targets in various somatic and psychiatric conditions (64, 72, 73).…”
Section: Discussionmentioning
confidence: 99%
“…Although ASIC2 is less well studied or lacked adequate power (70) compared to ASIC1a, there is evidence suggesting that ASIC2 works in concert and regulates neuroplasticity in the brain (71, 72). ASICs are considered potential drug targets in various somatic and psychiatric conditions (64, 72, 73).…”
Section: Discussionmentioning
confidence: 99%
“…The ASIC2b and ASIC4 subunits do not form functional proton-gated channels by themselves, but ASIC2b can associate with other ASIC subunits to confer new properties and regulations to heterotrimeric channels [ 13 , 23 , 24 ]. ASIC currents are generally transient even if the acidification is maintained, but a sustained phase is associated with expression of ASIC3 or with the presence of the ASIC2b subunit in heterotrimers ( Figure 2 ).…”
Section: Molecular and Functional Properties Of Asicsmentioning
confidence: 99%
“…As outlined in the previous section, ASICs are widely expressed in the mammalian nervous system in general and the brain in particular. The list of established functions of this receptor family is already long and is rapidly increasing (for instance, reviewed in [ 102 , 103 ]). ASICs are involved in many important physiological functions, as well as contributing to a variety of pathologies.…”
Section: Asics In Brain Pathologymentioning
confidence: 99%